Prinsip dan Asas Masyarakat Multikultural Perspektif Tariq Ramadan - Saumantri, Theguh (Sophist : Jurnal Sosial Politik Kajian Islam dan Tafsir, 2023)
Pluralism and inclusivity are important aspects that need to be understood in the context of today’s multicultural society. However, in pluralistic societies, conflicts often arise due to differences and disagreements among different groups. This study aims to analyze the concepts of pluralism and inclusivity in the thoughts of Tariq Ramadan, with a focus on the concepts of European Muslim and Dar al-Shahadah. This research is a literature study with a philosophical approach that aims to examine the ideas and concepts of the figure. The results of this study indicate that in his thinking, Tariq Ramadan emphasizes the importance of a critical, inclusive, and pluralistic approach to Islam as well as advocating for reform in Islamic thought. His concepts of European Muslim and Dar al-Shahadah offer a positive view of the role of Muslim identity in an increasingly complex and changing global context in creating a more just and harmonious society and teaching the importance of recognizing and respecting the truth and human rights in all regions of the world, regardless of religious and cultural differences.